PENGARUH PERMAINAN BAKIAK TERHADAP KEMAMPUAN MOTORIK KASAR PADA ANAK USIA 5-6 TAHUN DI PAUD AS-SHIFA CITRA KECAMATAN TAMPAN KOTA PEKANBARU - Sevtri Dani Siska; Daviq Chairilsyah; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations on the ability of gross motor students have not developed optimally. So it is necessary to apply the use of bakiak game. This study aims to determine the effect of bakiak on gross motor skills in children aged 5-6 years in Paud As Shifa Citra Tampan District City of Pekanbaru. The sample used in this study was 20 students. The data collection techniques used are observation and documentation. Data analysis technique used t-test with SPSS 20.0. The research hypothesis is the activity of the use of bakiak game has an effect on gross motor skills in children aged 5-6 years in Paud As Shifa Citra Tampan District City of Pekanbaru. This can be known from the analysis of data obtained thitung = 15.550 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is a difference in ability to recognize the concept of the number of students significantly after the use of bakiak game in learning. So it means Ho is rejected and Ha accepted which means there is a very significant difference between before and after doing experiments by applying the use of bakiak game. The influence of the usage of bakiaks on motor skills roughly aged 5-6 years in Paud As Shifa Citra Tampan District City of Pekanbaru by 58.99%.Keywords: Ability To Gross Motor Skills, Bakiak Games